2018
DOI: 10.1017/s0007114518000314
|View full text |Cite
|
Sign up to set email alerts
|

Starch synthase IIIa and starch branching enzyme IIb-deficient mutant rice line ameliorates pancreatic insulin secretion in rats: screening and evaluating mutant rice lines with antidiabetic functionalities

Abstract: Diabetes mellitus is a metabolic disease spreading worldwide that has been reported to worsen the development and progression of other diseases (cancer, vascular diseases and dementia). To establish functional rice lines with anti-postprandial hyperglycaemic effects, we developed mutant rice lines, which lack one or two gene(s) related to starch synthesis, and evaluated their effects. Powder of mutant rice lines or other grains was loaded to rats fasted overnight (oral grain powder loading test). Incremental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…RS content in steamed rice with the OsSBEIIb mutant is high ( Tsuiki et al 2016 ). Further, Tanaka et al (2018) reported that starch synthase IIIa and SBEIIb -deficient mutant rice could ameliorate pancreatic insulin secretion in rats. These results are consistent with our previous studies of Jiangtangdao 1 with sbe3-rs .…”
Section: Discussionmentioning
confidence: 99%
“…RS content in steamed rice with the OsSBEIIb mutant is high ( Tsuiki et al 2016 ). Further, Tanaka et al (2018) reported that starch synthase IIIa and SBEIIb -deficient mutant rice could ameliorate pancreatic insulin secretion in rats. These results are consistent with our previous studies of Jiangtangdao 1 with sbe3-rs .…”
Section: Discussionmentioning
confidence: 99%
“…Water-soluble metabolites in the rat primary hepatocyte lysate were analyzed according to a previously described protocol [24]. Same-cell concentrations of primary hepatocytes of ExHC and Congenic rats were collected in PBS and then sonicated to obtain the cell lysate.…”
Section: Analysis Of Water-soluble Metabolites In the Rat Primary Hepmentioning
confidence: 99%
“…Same-cell concentrations of primary hepatocytes of ExHC and Congenic rats were collected in PBS and then sonicated to obtain the cell lysate. This lysate (50 μl) was used for the metabolome analysis performed as described previously [24]. Metabolites extracted from cell lysate were derivatized with Methoxyamine hydrochloride and N-Methyl-N-trimethylsilyl-trifluoroacetamide and detected with gas chromatography mass spectroscopy analysis (GCMS-QP2020, SHIMAZU).…”
Section: Analysis Of Water-soluble Metabolites In the Rat Primary Hepmentioning
confidence: 99%
“…AC is a major component determining the eating and cooking quality (Tian et al ., ). At present, high‐RS rice, which is usually generated through deficiency of SSSIIIa or SBEIIb in rice, has high AC in kernels (Butardo et al ., ; Yang et al ., ; Zhu et al ., ; Zhou et al ., ; Itoh et al ., ; Tanaka et al ., ; Wada et al ., ). However, rice kernels with greater AC become more difficult to cook and harder, drier in texture, resulting in a poor cooking and eating quality.…”
Section: Introductionmentioning
confidence: 98%